TINJAUAN YURIDIS TERHADAP KEPEMILIKAN SERTIFIKAT TANAH DI WILAYAH PESISIR PANTAI DESA LAMU KECAMATAN BATUDA’A PANTAI - HARUN, YUSRIN M.; JUNUS, NIRWAN; SARSON, MOH. TAUFIQ ZULFIKAR; KADIR, MUHAMAD KHAIRUN KURNIAWAN; MAMU, KARLIN Z.; ELFIKRI, NURUL FAZRI (GANEC SWARA, 2024)
Usually the document showing this right is considered a land certificate. The aim of this research is to find out what drives people to make land title certificates in coastal areas and what the impact of these certificates is. A method called empirical legal research was used to conduct this research. Roger Cottrell said that empirical juridical research is a way of studying law that involves collecting and analyzing real-world information about legal issues, legal practices, and legal institutions. The goal is to learn how the law works in society and find better ways to solve legal problems. The research results show that there are legal problems in making land title certificates in coastal areas and that people who own them can be subject to sanctions by the government. These problems include not socializing with other people and the fact that the certificate can be revoked